Investigating The Theme Of The Short Story Entitled “A Good Man Is Hard To Find” By Flannery O’Connor - Agnes Br; Rajeg, I Made; Maharani, Sang Ayu Isnu (Denpasar Institute, 2024)
This article investigates the complex themes in Flannery O'Connor's